Mammalian Artificial Chromosomes Methods and Protocols - Sgaramella, Vittorio; Eridani, Sandro; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 2004)
Assembly of the basic units of mammalian chromosomes into artificial constructs, and the reduction of their components to more manageable dimensions, has now become a reality. In Mammalian Artificial Chromosomes: Methods and Protocols, leading scientists in cell biology, genetics, cell culturing, and gene transfer present their most productive methods for the preparation, characterization, and use of artificial chromosomes. The authors cover all relevant areas of artificial chromosome research-from basic genetics to daring attempts at building new gene therapy tools-and describe possible applications in genetic manipulation requiring large portions of the genome. Each fully tested protocol is described in step-by-step detail and includes a background introduction outlining the principle behind the technique, reagent and equipment lists, and tips on troubleshooting and how to avoid pitfalls. Cutting-edge and much-needed, Mammalian Artificial Chromosomes: Methods and Protocols offers a timely collection of meticulous techniques that will help elucidate the mechanisms of nuclear duplication, allow the introduction of changes into the human genome, and revolutionize our understanding of how chromosomes work.
From Natural to Artificial Chromosomes -- Methodologies Applied to Domestic Animal Chromosomes -- Mapping of the Hotspots of Recombination in Human DNA Cloned as Yeast Artificial Chromosomes -- Genomic Imprinting and Its Effects on Genes and Chromosomes in Mammals -- Centromeres and Neocentromeres -- Identification of Start Sites of Bi-Directional DNA Synthesis at Eukaryotic DNA Replication Origins -- Telomere Length Analysis and In Vitro Telomerase Assay -- Telomerization of Mammalian Cells and Transplantation of Telomerized Cells in Immunodeficient Mice -- Chromosome-Based Vectors for Mammalian Cells -- Mammalian Artificial Chromosome Formation in Human Cells After Lipofection of a PAC Precursor -- Use of Natural and Artificial Chromosome Vectors for Animal Transgenesis -- Pronuclear Microinjection of Purified Artificial Chromosomes for Generation of Transgenic Mice -- Modification of Human Bacterial Artificial Chromosome Clones for Functional Studies and Therapeutic Applications.
Keywords: Human genetics; Human Genetics